Advances and Current Challenges in Intestinal in vitro Model Engineering: A Digest - Costa, Joana; Ahluwalia, Arti (Frontiers in Bioengineering and Biotechnology, 2019)
The physiological environment of the intestine is characterized by its variegated composition, numerous functions and unique dynamic conditions, making it challenging to recreate the organ in vitro. This review outlines the requirements for engineering physiologically relevant intestinal in vitro models, mainly focusing on the importance of the mechano-structural cues that are often neglected in classic cell culture systems. More precisely: the topography, motility and flow present in the intestinal epithelium. After defining quantitative descriptors for these features, we describe the current state of the art, citing relevant approaches used to address one (or more) of the elements in question, pursuing a progressive conceptual construction of an “ideal” biomimetic intestinal model. The review concludes with a critical assessment of the currently available methods to summarize the important features of the intestinal tissue in the light of their different applications.